2018
DOI: 10.1177/0706743717752881
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of a High Support Housing Initiative for Persons with Severe Mental Illness and Long-Term Psychiatric Hospitalization

Abstract: This study suggests the High Support Housing Initiative is potentially cost saving relative to inpatient hospitalization at the Centre for Addiction and Mental Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Enfacing the number of persons in need of supported housing, economic considerations [26], and most of all the users' preferences [27], our main results implicate important considerations regarding mental health care policy and access to housing services for persons with a severe mental illness. As there appeared overall positive psychosocial and clinical outcomes regardless of the supported housing type, one can conclude that supported accommodation per se appears to be an effective rehabilitative care approach (compare to [1]).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Enfacing the number of persons in need of supported housing, economic considerations [26], and most of all the users' preferences [27], our main results implicate important considerations regarding mental health care policy and access to housing services for persons with a severe mental illness. As there appeared overall positive psychosocial and clinical outcomes regardless of the supported housing type, one can conclude that supported accommodation per se appears to be an effective rehabilitative care approach (compare to [1]).…”
Section: Discussionmentioning
confidence: 83%
“…All in all, the present findings seem to support the expansion of supported housing programs and ensuring the availability of affordable housing for people with mental health problems. This would not only be a reasonable future perspective under financial aspects [26,29,30], but also by taking the users' needs and wishes even more into account: a recent review and meta-analysis on the choice of housing in people with mental disorders revealed that 84% of the persons with severe mental illness preferred to live under more independent housing settings [27]. The importance of user preferences should not be underestimated, because studies have shown the positive effects of choice on psychosocial outcomes in mental health supported housing [31,32].…”
Section: Discussionmentioning
confidence: 99%